Progress on the efficacy and mechanism of action of panax ginseng monomer saponins treat toxicity - Wang, Xinyi; Wang, Rongcan; Qiao, Yongfei; Li, Yali (Frontiers in Pharmacology, 2022)
As a traditional Chinese medicine, Panax ginseng C. A. Meyer (PG) has preventive and therapeutic effects on various diseases. Ginsenosides are main active ingredients of PG and have good pharmacological effects. Due to the diversity of chemical structures and physicochemical properties of ginsenosides, Currently, related studies on PG monomer saponins are mainly focused on the cardiovascular system, nervous system, antidiabetic, and antitumor. There are few types of research on the toxin treatment, predominantly exogenous toxicity. PG and its monomer ginsenosides are undoubtedly a practical option for treating exogenous toxicity for drug-induced or metal-induced side effects such as nephrotoxicity, hepatotoxicity, cardiotoxicity, metal toxicity and other exogenous toxicity caused by drugs or metals. The mechanism focuses on antioxidant, anti-inflammatory, and anti-apoptotic, as well as modulation of signaling pathways. It summarized the therapeutic effects of ginseng monomer saponins on exogenous toxicity and demonstrated that ginsenosides could be used as potential drugs to treat exogenous toxicity and reduce drug toxicities.